2015
DOI: 10.1016/j.jallcom.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the thermal stability of Nd Y Zr1−−O2− inert matrix fuel materials

Abstract: An important step in achieving a closed uranium fuel cycle is to develop new inert matrix fuel (IMF) materials for use in the burn-up of transuranic species (TRU; i.e., Pu, Np, Am, Cm). Cubic fluorite zirconia (ZrO 2) has ideal properties for use in IMF applications, but it is not stable at room temperature and must be stabilized through the addition of small amounts of dopants such as Y. While Y-substituted zirconia (YSZ) has been extensively studied, relatively little work has been done to investigate how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 56 publications
4
41
0
Order By: Relevance
“…These results were compared to similar results from Nd-YSZ materials made via a ceramic method reported previously. 39 This study has shown that the local bonding structures around the metal centres in the materials made by the co-precipitation synthesis method or the ceramic synthesis method are similar. However, the intermediate and long-range structures of the materials made by the coprecipitation method were more disordered compared to the structures of the materials made by the ceramic method.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…These results were compared to similar results from Nd-YSZ materials made via a ceramic method reported previously. 39 This study has shown that the local bonding structures around the metal centres in the materials made by the co-precipitation synthesis method or the ceramic synthesis method are similar. However, the intermediate and long-range structures of the materials made by the coprecipitation method were more disordered compared to the structures of the materials made by the ceramic method.…”
Section: Introductionmentioning
confidence: 84%
“…48 These parameters are described in detail in previous publications. 39,48 The Zr K-edge EXAFS spectra were analyzed by calculating F j (k), j (k), and for each set of scattering pairs in a given cluster using the FEFF6 code. 49 The Zr-Zr and Zr-Y paths were considered as equivalent, due to the similar atomic number of Zr and Y.…”
Section: Zr K-and Y K-edge X-ray Absorption Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations